Green innovation in ports: drivers, domains, and challenges - Liu, Ying; Chao, Yiying; Xie, Shangwei; Wang, Guofeng; Wang, Lu; Xue, Cheng (Frontiers in Marine Science, 2025)
The transition toward sustainable maritime development has placed ports at the forefront of global green transformation. As critical nodes in maritime supply chains, ports are under growing pressure to reduce emissions, optimize resource use, and adopt digital technologies. While numerous green practices have emerged in recent years, the literature on port green innovation remains fragmented, lacking a comprehensive synthesis of its drivers, application domains, and systemic challenges. To address this gap, this study conducts a systematic review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, drawing on peer-reviewed publications from the Scopus and Web of Science databases. The analysis identifies three principal drivers of green innovation in ports: internal dynamics stemming from economic and technological capabilities, external pressures related to environmental regulation and policy, and societal expectations that steer transformation. Green innovation practices are classified into four functional domains: foundational measures, operational optimization, energy system transformation, and intelligent upgrading. In parallel, four major challenges are revealed: persistent ecological pressures, energy transition bottlenecks, fragmented regulatory frameworks, and operational trade-offs. This review contributes an integrated analytical framework that clarifies the conceptual landscape of port green innovation and offers actionable insights for research, policy, and strategic planning.